Role of Forests in Flood Control Paper for Central Water and Power Commission - Singh, B. (Indian Forester, 1955)
Floods have caused tremendous damage in the past: the principle reason being that the hill slopes have been stripped off of their vegetative cover. The rainfall being mostly limited to short periods in the year takes the form of highly concentrated showers at times. Regulation of run-off is, therefore, essential in the interests of flood control. Dense vegetative cover provides effective check against rapid run-off, floods and consequently decrease in transportation of silt. This paper is written with particular reference to Bhakhra-Nagal Project. The Bhakhra reservoir will receive the drainage of 7657.7 square miles out of which forest area amounts to 775 square miles only. This works out to 10% of the total catchment of the reservoir. The highest part of the catchment in Sipiti is badly denuded. The conditions of the catchment in Suket Forest Division is deplorable. Large tracts of sloping hills have been laid bare of forest cover. For proper flood control, afforestation and Soil Conservation measures are essential in the catchment. The cost of operations is estimated @ 15 crores which works out to 9% of the capital out-lay on the Bhakhra Project. It is worthwhile spending the amount spread over a number of years in the interest of the successful working of the Project.